Efficacy of Microbial Concortia with Liquid Organic Fertilizer for Leaf Spot Disease Control on Oil Palm Nursery - Akhmad Faisal Malik; Tiara Dwi Nurmalita; Anastastia Raditya Hidayanti (International Journal of Oil Palm, 2022)
Leaf spot is the primary disease on oil palm nurseries. The symptom of the disease is leaf spots are round to oval in shape and vary in color from yellow to brown to black. The initial size may be as small as a pin point. Some leaf spots initially appear as lesions. During disease development, leaf spots will have a contrasting colored edge or halo - e.g., brown spot with a yellow halo, tan center with brown edge or gray center with black edge and a yellow halo. As the leaf spots expand in size, the shape and coloration may change. As the disease progresses, leaf spots often coalesce (merge together) to form large areas of blighted tissue. If the disease continues to develop, leaflets or the entire leaf may die prematurely. The disease also causes stunted and even plant death. Disease control methods that rely primarily on biological agents and do not include fertilizers are less effective in the field. Therefore, the development of organic fertilizer formulations and the use of biocontrol agents are expected to assist oil palm nurseries in suppressing leaf spot disease. The purpose of this study is to investigate the effect of organic fertilizer and biocontrol agents on leaf spot disease. The results showed that the treatment of Organic Fertilizer and biocontrol agents was able to reduce 47.19% leaf spot disease after five weeks of application.